2018
DOI: 10.1186/s13550-018-0409-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoromisonidazole predicts evofosfamide uptake in pancreatic tumor model

Abstract: BackgroundQuantitative imaging can facilitate patient stratification in clinical trials. The hypoxia-activated prodrug evofosfamide recently failed a phase III trial in pancreatic cancer. However, the study did not attempt to select for patients with hypoxic tumors. We tested the ability of 18F-fluoromisonidazole to predict evofosfamide uptake in an orthotopic xenograft model (BxPC3).MethodsTwo forms of evofosfamide were used: (1) labeled on the active moiety (3H) and (2) on the hypoxia targeting nitroimidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Such a strategy involving FMISO-CLI would allow a rapid selection of subjects with positive hypoxic signal in order to successfully evaluate hypoxia-targeting drugs. This was recently highlighted by Grkovski et al who suggested that the poor outcome of the MAESTRO trial, evaluating the hypoxia-activated evofosfamide, was partly due to the inclusion of non-hypoxic tumours, which may have masked the benefit of the drug [5]. Such a result shows that not only CLI is relevant to assess tumour hypoxia, but also for preclinical drug development due to its high throughput capabilities also reported elsewhere [8].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Such a strategy involving FMISO-CLI would allow a rapid selection of subjects with positive hypoxic signal in order to successfully evaluate hypoxia-targeting drugs. This was recently highlighted by Grkovski et al who suggested that the poor outcome of the MAESTRO trial, evaluating the hypoxia-activated evofosfamide, was partly due to the inclusion of non-hypoxic tumours, which may have masked the benefit of the drug [5]. Such a result shows that not only CLI is relevant to assess tumour hypoxia, but also for preclinical drug development due to its high throughput capabilities also reported elsewhere [8].…”
Section: Discussionmentioning
confidence: 92%
“…Biomarkers of tumour hypoxia allow to improve the drug development process through the selection of individuals potentially eligible for therapies that target hypoxic environment in both preclinical and clinical settings [5]. FMISO is a well-known PET radiotracer of tumour hypoxia [3] able to produce a CR due to the emission of a positron with a maximal energy of 633 keV [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, screening methods need to be developed based on tumor hypoxia to select the best candidates for this type of therapy. A growing number of studies have shown that PET/CT imaging can be an effective method to monitor HAPs uptake and therapeutic response ( 148 , 190 , 192 ). Second, biomarkers to predict drug sensitivity are needed.…”
Section: Conclusion and Suggestions For Future Investigationsmentioning
confidence: 99%
“…In this context, we propose that imaging of hypoxia may help with patient stratification and therapy monitoring (19)(20)(21)(22). To this end, different magnetic resonance imaging (MRI)-and positron emission tomography (PET)-imaging based analyses have been explored to identify tumor hypoxia (23,24) and predict response to HAPs in pre-clinical models (19,25).…”
Section: Introductionmentioning
confidence: 99%